Rancang bangun Sistem Informasi Kerjasama Universitas Kristen Satya Wacana - Fredrik Landjamara Ndjurumana; Evangs Mailoa (Fakultas Teknologi Informasi Universitas Kristen Satya Wacana, 2020)
In order to improve institutional capabilities, UKSW needs to collaborate with various parties. Documents of agreement which is the references of implementation must be archived and managed properly. The document of agreement in UKSW, still manage manually, making it difficult to find complete data related to the cooperation agreement that has been made by UKSW. Information technology has an important role in increasing the efficiency and effectiveness of the document management and archiving. This study aims to develop a cooperation information system that capable to record the whole process of submitting agreement, until the process of archiving the signed document. Rapid Application Development (RAD) method used with the aim of accelerating development process, providing good quality of system, and reducing development and maintenance costs. The result of this research is a cooperation information system that has been implemented at UKSW Salatiga.